Penggunaan Kecerdasan Buatan (Ai) Dalam Penulisan Berita pada Portal Berita A-News - Ikhwan Alif; Muh. Akbar; Moehammad Iqbal Sultan (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to examine the use of artificial intelligence (AI) in news writing on the A-News portal. The research employs a qualitative method with a descriptive research design. The findings indicate that the study explores the application of artificial intelligence (AI) in news production at A-News using qualitative methods and agency theory. A-News utilizes AI to accelerate news production, although the main challenge lies in ensuring the accuracy and reliability of information. The newsroom emphasizes transparency in news production and strives to enhance interaction with readers. Although AI increases efficiency, A-News limits its use to maintain journalistic independence and creativity, acknowledging the technology’s limitations. This research provides insight into the implementation of AI in newsroom workflows and the challenges faced in integrating artificial intelligence into journalism.